Immigration Arrangements Indonesian Citizen Travel Document perspective - Made Maharta Yasa; I Gde Putra Ariana; Anastasya Puspa Dewi; Yustikarini Tri Utami Dewi (Focus Journal : Law Review, 2024)
This research aims to research, analyze and examine Immigration Regulations from the perspective of Indonesian Citizen Travel Documents. Based on Law no. 6 of 2011 concerning Immigration, foreigners when traveling in Indonesia are required to have travel documents, travel documents are official letters issued by authorized officials from a country. The research method used in this research is the normative legal research method. The results of the discussion show that regulations regarding travel documents for Indonesian citizens are regulated in Law Number 6 of 2011 concerning Immigration as an umbrella rule for immigration legislation. In Article 1 number 13, number 15 and number 16 of the Immigration Law, the meaning of travel documents, the meaning of travel documents of the Republic of Indonesia and Passports of the Republic of Indonesia are given. In full it states: Article 1 number 13, namely: Travel Documents are official documents issued by authorized officials from a country, the United Nations, or other international organizations for travel between countries which contain the identity of the holder. Article 1 number 15: Travel Documents of the Republic of Indonesia are Passports of the Republic of Indonesia and Travel Documents are Like Passports of the Republic of Indonesia. Article 1 number 16: Passport of the Republic of Indonesia, hereinafter referred to as Passport, is a document issued by the Government of the Republic of Indonesia to Indonesian citizens to travel between countries which is valid for a certain period of time. The same regulation is also contained in Government Regulation Number 40 of 2023 concerning the Fourth Amendment to Government Regulation Number 31 of 2023 concerning Implementing Regulations of Law Number 6 of 2011 concerning Immigration.